Molecular survey on cattle and sheep hydatidosis and first detection ofEchinococcus canadensis(G6/G7) in sheep in Turkey - Mehmood, Sarfraz; Simsek, Sami; Celik, Figen; Kesik, Harun Kaya; Kilinc, Seyma Gunyakti; Ahmed, Haroon (Cambridge Univ Press, 2020)
Larval stage of genus Echinococcus is the causing agent for the zoonotic infection which is life threatening known as Echinococcosis. The purpose of this study was the identification, molecular analysis and characterization ofEchinococcusspp. in sheep and cattle. The sampling was done from slaughterhouse of Elazig, Turkey. A total of 85 isolates (sheep,n= 19 and cattle,n= 66) have been collected after slaughtering. Following the gDNA isolation and PCR products of mt-CO1 gene (446 bp) of all the samples were sequenced. Out of 85 isolates, 84 were recognized asEchinococcus granulosus sensu strictoand one sheep isolate was found asEchinococcus canadensis(G6/G7 ) which is identified for the first time in Turkey. However, single nucleotide polymorphism has been observed not only in samples of different animals but also in samples collected from the same cattle. Six liver and three lung hydatid cysts have been detected in cattle. Although no nucleotide differences have been observed in the liver samples, there was single nucleotide polymorphism (C -> T) in 40th nucleotide of two lung cysts. As a result of haplotype analysis, 16 haplotypes ofE. granulosus s.s.were detected in 66 cattle isolates whereas 7 haplotypes ofE. granulosus s.s.were identified in 19 sheep samples.
Keywords: Cattle; Echinococcus granulosus; haplotype; PCR; sequence; sheep; Turkey